Freedom of Expression in Critical Content on Public Infrastructure via Social Media - Chusnul Khitam, Muhammad; Isnaini, Enik; Rizkiyah, Putri Ainiyatur (Jurnal Independent, 2025)
Freedom of speech is the right of every person to express their opinions regarding criticism, suggestions, and opinions. One form of conveying criticism is by creating content related to public infrastructure. Based on this background, the author proposes a formulation of the problem, namely, first, how are the legal rules for freedom of speech on social media. Second, how is the legal protection for content creators criticizing public infrastructure on social media. This research method uses a normative juridical research type, with a statute approach. The legal materials used are primary legal materials including: the 1945 Constitution, Law Number 9 of 1998, Law Number 39 of 1999 and Law Number 1 of 2024, the second amendment to Law Number 11 of 2008. From the results of the study, it can be concluded that: the legal rules for freedom of opinion on social media are regulated in Article 28E paragraph (3) of the 1945 Constitution, regulated in Article 1 paragraph (1) of Law Number 9 of 1998 and in Article 23 paragraph (2) of Law Number 39 of 1999. And legal protection for creators of content criticizing public infrastructure is regulated in Article 28F of the 1945 Constitution and regulated in Article 14 paragraph (2) of Law Number 39 of 1999, and based on the Constitutional Court Decision Number 105/PUU-XXII/2024. Given that the rights that a person has carry the consequence of an obligation to respect the rights of others or with society, then this right does need to be limited. This limitation is regulated in Law Number 1 of 2024, the second amendment to Law Number 11 of 2008, where this limitation also plays a role as an ethic in interacting through various media, one of which is social media.